Depot-medroxy progesterone acetate as contraceptive: study at tertiary care centre - Gupta, Neena; Diwedi, Divya; Sharma, Neha; Jahan, Uruj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The aim was to study the acceptability, efficacy and side effects of Depot-medroxy progesterone acetate (DMPA) as contraceptive in postpartum, interval and postabortal period. Methods: The present study was a prospective longitudinal study conducted in the department of obstetrics and gynaecology, GSVM medical college, Kanpur. Total 300 patients were counselled out of which 141 enrolled in the study during a period of January 2019 to September 2020. All reproductive age group (18-45) women who were willing to use DMPA for contraception in postpartum period, postabortal period or in interval period and also ready for follow up were included in the study. At the time of 1st dose DMPA card issued to patient where her particulars, weight, blood pressure, menstrual complaints were recorded. Date of next visit was also mentioned. Results: Despite of benefits and proper counselling, less number of patients (47%) opted for DMPA as contraception. Acceptance (55%) and continuation rate for further doses (36.3% for 4th dose) was maximum in the postpartum period among the three groups taken in our study (postpartum, interval and postabortal). Menstrual changes were the most common reasons for discontinuation (39.7%) in all three groups. Other minor side effects may include change in weight and mood swings. Conclusions: When patients were counselled immediately after delivery, many of them gave positive note, but actual time of application is after 6 weeks postpartum where less number of patients turned up for DMPA. There is a need to create awareness regarding the harmless side effects.